Transcutaneous auricular neurostimulation to reduce heavy menstrual bleeding in women with and without von Willebrand disease - Czura, Christopher J.; Weyand, Angela C.; Baldwin, Maureen K.; Recht, Michael; McWade, Melanie A.; Covalin, Alejandro; Khodaparast, Navid (Frontiers in Medicine, 2025)
Prior studies have revealed that electrical stimulation of the vagus nerve modifies platelet phenotype and reduces blood loss in preclinical models of soft tissue injury. This pilot trial (NCT06064851) sought to determine whether the use of a wearable transcutaneous auricular neurostimulation (tAN) device targeting both the vagus and trigeminal nerve branches correlated with reduced menstrual blood loss in participants with or without von Willebrand disease (VWD). Participants with qualified heavy menstrual bleeding (HMB) gave informed consent to participate in an IRB-approved, decentralized, open-label pilot trial. Participants were followed for two consecutive menstrual cycles. During the baseline menstruation, participants estimated daily blood loss using a validated pictorial blood loss assessment chart (PBAC). During the treatment menstruation, participants self-administered two daily 1-h sessions of tAN daily throughout menstruation and estimated daily blood loss with the PBAC. The PBAC was also used to calculate duration of each menstruation. Student’s paired T-test was used to compare mean PBAC scores between menstruations. In participants (n = 8) with von Willebrand disease and HMB, use of tAN is associated with 57% lower PBAC scores. Participants with heavy menstrual bleeding of unknown cause (HMBu; n = 8) experienced 54% lower PBAC scores while using tAN. Use of tAN also reduced duration of menstruation in both cohorts by 19%. Reductions in menstrual symptoms including cramp and other pain and fatigue and increases in health-related quality of life scores were also noted with use of tAN. tAN activates the vagal and trigeminal networks which are thought to modulate platelet phenotype and lead to improved hemostasis. These pilot results suggest that tAN may be effective in reducing menstrual blood loss in HMB, including those with VWD using concomitant hormonal therapies.